A importância da marca como um dos instrumentos de fomento do desporto - Piragini, Ricardo (2018)
The present dissertation aims to provide a reflection on the current scenario that supports the world sporting events, which increasingly require large investments for their execution, depending on the contributions of the governments that host them and, mainly, on the generation of own revenues, through sponsorship and partnerships. As states are not always able to fully finance all investments, the organizers use the exploitation of intellectual property assets for this purpose, thus requiring exceptional privileges, which will be discussed below. The question that arises refers to the sports marketing used as an instrument of viabilization of the sport activity addressing the complex relationship that is established between sponsors, athletes and clubs. Considering the aspect of the brands, the methodological didactic section delimits the field of study in the construction of the brand used by the sports organization and organization and its marketing developments. In order to reach the objective outlined, it will be necessary to apply a qualitative study methodology, and the research will be bibliographical, doctrinal, concluding with a case study in interview format, especially under comparative law bias